2020
DOI: 10.12659/msm.921584
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Monocyte Chemotactic Protein 1 Variants and Age-Related Macular Degeneration Onset Among Chinese People

Abstract: Departmental sources Background:We assessed the potential association between monocyte chemotactic protein 1 (MCP-1) variants (rs1024611 and rs3760396) and age-related macular degeneration (AMD) susceptibility among Chinese Han people. Material/Methods:Our research included 129 AMD patients and 131 healthy controls. Genotyping for MCP-1 variants was performed in the 2 groups, and genotype and allele distributions were checked between groups by c 2 analysis. Odds ratio (OR) and 95% confidence interval (CI) refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(26 reference statements)
1
0
0
Order By: Relevance
“…This study found that the G allele at the CCL2 promoter polymorphism rs1024611 was more common in early AMD. Our study confirmed findings in the Chinese Han population of 129 AMD patients and 131 healthy volunteers, as they also found an increased incidence of AMD with the rs1024611 GG genotype and a significantly higher frequency of the rs1024611 G allele in AMD patients [ 45 ]. In addition, allele frequency analysis in the Indian population confirmed that the G allele was also more common in AMD patients than in the control group [ 35 ].…”
Section: Discussionsupporting
confidence: 90%
“…This study found that the G allele at the CCL2 promoter polymorphism rs1024611 was more common in early AMD. Our study confirmed findings in the Chinese Han population of 129 AMD patients and 131 healthy volunteers, as they also found an increased incidence of AMD with the rs1024611 GG genotype and a significantly higher frequency of the rs1024611 G allele in AMD patients [ 45 ]. In addition, allele frequency analysis in the Indian population confirmed that the G allele was also more common in AMD patients than in the control group [ 35 ].…”
Section: Discussionsupporting
confidence: 90%